High Prevalence and Predominance of Hepatitis Delta Virus Genotype 1 Infection in Cameroon - Foupouapouognigni, Yacouba; Noah, Dominique Noah; Sartre, Michèle Tagni; Njouom, Richard (Journal of Clinical Microbiology, 2011)
Antibodies to the hepatitis delta virus (HDV) were found in 17.6% of 233 hepatitis B virus surface antigen-positive subjects in Cameroon. Phylogenetic analyses showed the presence of HDV-1, HDV-5, HDV-6, and HDV-7 genotypes. These results enrich the limited data on HDV prevalence and molecular diversity in Cameroon.